Empowerment of youth peer groups in improving breast cancer awareness in high school in Samarinda - Rahayu, Eka Putri; Chifdillah, Nino Adib; Tonapa, Emelia (Faculty of Medicine, Public Health, and Nursing, Universitas Gadjah Mada, 2025)
Introduction: Breast cancer is the type of cancer that has the highest contribution to the prevalence of cancer of women in Indonesia. This type of cancer has a high mortality rate due to late early detection. Breast cancer is the most common cancer in women. Early detection of breast cancer plays significant role in reducing mortality and improving patient prognosis. Based on initial data taken, the knowledge results of 10th grade were obtained SMA Negeri 1 Samarinda reached 52,5% which is classified as knowledge level (less <56%). Apart from that, the percentage of 10th grade high school students who have a family history of breast cancer is 15%. the percentage of of early menstruation in 10th grade high school students is 28%. Therefore, it is necessary to continue to be reminded of health information about breast cancer. The aim is to provide students with an understanding of breast cancer, its impact, and risks, and to create facilities to increase this knowledge.Methods: The purpose of this community service was to community empowerment through youth peer groups regarding breast cancer awareness. The community service methods were health education about breast cancer awareness and Breast Self Examination (BSE) demonstrations. The population in this study were female students in 10th grade. The sample was 94 respondents. Primary data of this study were collected using a pre and post-test questionnaire. The data analysis used was the percentage and frequency.Results: The results obtained an increase in knowledge of students after being given breast cancer awareness education whereas 78,7% in the good category increased to 88,3%.Conclusion: With increasing levels of knowledge, hopefully, it will be possible for adolescent’s attitudes towards Breast Self Examination (BSE).